Dissociation of antibody responses during human schistosomiasis and evidence for enhancement of granuloma size by anti-carbohydrate IgM. - Simpson, A; Yi, X; Lillywhite, J; Ali, P; Kelly, C; Mott, R; Smithers, SR; Oliveira, R; Katz, N; Rumjanek, F (1990)
Immunoglobulin (Ig) G and IgM antibody levels to soluble egg antigens (SEA), adult worm glycoproteins (AWGP), carbohydrate antigens (CHO) and cationic exchange fraction 6 (CEF6) were measured in serum specimens taken from Brazilian patients with acute, intestinal, hepato-intestinal and hepatosplenic schistosomiasis mansoni. The antibody levels varied among the groups, with the highest anti-egg antigen responses in the acute patients and the highest anti-adult worm responses in patients with chronic disease. The responses to the component parts of the egg antigens were dissociated, with anti-carbohydrate IgG and IgM responses being highest in the acute infection group and anti-CEF6 IgG responses being uniform among the clinical groups. The possibility of a direct role for anti-CHO antibody responses in egg-induced pathology was investigated using the mouse lung model. The anti-carbohydrate monoclonal antibody NIMP/M45 significantly enhanced granuloma formation. Mice given NIMP/M45 produced granulomas larger than those of naive mice or mice given an unrelated monoclonal antibody, and as large as those produced by mice which had been presensitized to egg antigens. The independent regulation of responses to egg antigens may indicate that such responses are minimized to reduce the pathological consequences of infection whilst allowing the development of protective anti-worm responses.